SOCIAL PRODUCTION OF URBAN SPACE AND PRODUCTION OF INEQUALITY IN THE CITY - Sousa, Michele de (2018)
This paper aims to reflect on the production of urban space in contemporary capitalism, highlighting the relationship about forms and processes of differentiation, inequality and socio-spatial fragmentation, segregation and self-segregation. This is a theoretical reflection. Thus, throughout the text, some points for discussion about the process of production of urban space are highlighted, starting from the sociospatial differentiation and inequality that can be deepened in other processes that are revealed in the forms and contents of cities and are engendered by public and private agents in an effort to attend the needs of capital. In addition, it was sought to refer to how these processes can be apprehended at different levels and scales. It appears that the production of the city is made, designed and planned unevenly. The materiality of this city, its forms and structures, expresses such inequality and conditions at